Gender inequalities in political participation and political engagement among young people in Europe: Are young women less politically engaged than young men?. (February 2022) - Grasso, Maria; Smith, Katherine
This paper contributes to the literature by examining gender inequalities in political participation and political engagement among young people from a comparative perspective. By analysing data on young people from nine European countries collected in 2018, we examine gender inequalities in participation in various modes of conventional and unconventional activism as well as related attitudes, broader political engagement and key determinants, cross-nationally, in order to provide a detailed picture of the current state of gender inequalities in political activism among young people in Europe. Our results allow us to speak to extant theorising about gender inequalities by showing that the extent of political inequality between young men and women is less marked than one might expect. While the gender gaps in political participation for activities such as confrontational types of protest are small or absent, we find that young women are actually more active in petitioning, boycotting, and volunteering in the community. Young men instead are more active than young women in a majority of the nine countries analysed with respect to more institutional forms of participation linked to organizations and parties, various types of online political participation, and broader political engagement measures, such as internal political efficacy and consumption of political news through various channels. However, young men also appear to be more sceptical at least of certain aspects of democratic practice relative to young women.